How suitable is lithium-sulphur battery for electric city bus application? - Calvo-Serra, Victor; Fotouhi, Abbas; Soleymani, Mehdi; Auger, Daniel J. (Inderscience, 2020)
Lithium-sulphur (Li-S) battery is a promising alternative for the existing battery technologies in the market. This paper investigates application of a new prototype Li-S cell in an electric city bus. For this purpose, MATLAB/Simulink software has been employed to build and simulate a vehicle model according to the specifications of available electric buses in London city. An equivalent circuit cell model is parameterised based on experimental data. Battery pack sizing is then performed and the Li-S technology is compared with two commercial Li-ion batteries used in existing electric buses in London city. The results demonstrate that the proposed Li-S battery pack can fulfil the requirements of an electric city bus in terms of power while achieving a considerable increase in vehicle's range. However, Li-S cell prototypes still suffer from limited cycling life that prevents this technology to be commercialised for such an application at the time being.
Keywords: lithium-sulphur cell; modelling; battery pack sizing; simulation; electric bus